Rethinking Marine Tourism Safety in Nusa Penida: A Qualitative Study of Risks and Management Strategies - Rahman, Ari; Suryawan, I Wayan Koko (Indonesian Journal of Tourism and Leisure, 2025)
Marine tourism in Nusa Penida, Bali, has expanded rapidly over the past decade, attracting large numbers of domestic and international visitors to its renowned dive sites, coral reefs, and coastal landscapes. However, this growth has raised critical safety concerns that threaten both visitor well-being and the sustainability of the destination. This qualitative study draws on an extensive literature review and a structured hypothetical survey framework, designed in August 2024, to examine the systemic challenges in marine tourism safety. Rather than relying on newly collected empirical data, this research synthesizes existing reports, stakeholder commentary, and regulatory reviews to identify ten interrelated categories of risk: weak enforcement, poor infrastructure, unregulated tourism expansion, unsafe operator behavior, limited monitoring, environmental degradation, weather-related risks, lack of safety education, poor incident reporting, and fragmented governance. Through thematic analysis, the study links these issues to feasible and locally adaptive solutions, highlighting the need for integrated zoning, multilingual safety communication, institutional collaboration, and climate-responsive infrastructure. The findings underscore the urgency of developing cross-sectoral, adaptive marine safety governance that aligns tourism growth with environmental resilience and visitor protection. Policy recommendations are proposed for application in other high-risk coastal destinations